2021
DOI: 10.3390/cancers13102441
|View full text |Cite
|
Sign up to set email alerts
|

Cathepsin K: A Novel Diagnostic and Predictive Biomarker for Renal Tumors

Abstract: Cathepsin K is a papain-like cysteine protease with high matrix-degrading activity. Among several cathepsins, cathepsin K is the most potent mammalian collagenase, mainly expressed by osteoclasts. This review summarizes most of the recent findings of cathepsin K expression, highlighting its role in renal tumors for diagnostic purposes and as a potential molecular target. Indeed, cathepsin K is a recognized diagnostic tool for the identification of TFE3/TFEB-rearranged renal cell carcinoma, TFEB-amplified renal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 71 publications
2
17
0
Order By: Relevance
“…In addition to the classic immunohistochemical markers mentioned above, specific immunohistochemical markers of PEComa have been explored in the recent years, and it has been found that cathepsin K and at least one muscle marker are expressed in all PEComas 39 . This is consistent with the results of Caliò et al's study that suggested that cathepsin K may be related to TFE3 rearrangement and mTOR pathway activation and may be used as a target for drug therapy in the future 40 . Caliò et al also proposed that parvalbumin is expressed in many cases and can even be used as an immune marker for EAML lesions 41 .…”
Section: Diagnosis Of Renal Epithelioid Angiomyolipomasupporting
confidence: 89%
See 1 more Smart Citation
“…In addition to the classic immunohistochemical markers mentioned above, specific immunohistochemical markers of PEComa have been explored in the recent years, and it has been found that cathepsin K and at least one muscle marker are expressed in all PEComas 39 . This is consistent with the results of Caliò et al's study that suggested that cathepsin K may be related to TFE3 rearrangement and mTOR pathway activation and may be used as a target for drug therapy in the future 40 . Caliò et al also proposed that parvalbumin is expressed in many cases and can even be used as an immune marker for EAML lesions 41 .…”
Section: Diagnosis Of Renal Epithelioid Angiomyolipomasupporting
confidence: 89%
“…39 This is consistent with the results of Caliò et al's study that suggested that cathepsin K may be related to TFE3 rearrangement and mTOR pathway activation and may be used as a target for drug therapy in the future. 40 Caliò et al also proposed that parvalbumin is expressed in many cases and can even be used as an immune marker for EAML lesions. 41 Moreover, PNL2 has been shown to be a biomarker of sensitivity and specificity in melanoma; recently, some scholars have found that compared with HMB-45, PNL2 has a higher vs. 81%) and has specificity in malignant PEComa (89% vs. 81%).…”
Section: Histopathological Examinationmentioning
confidence: 99%
“…To distinguish them, cathepsin K and parvalbumin are very helpful, in addition to CK7 and S100A1 for chromophobe renal cell carcinoma [ 47 , 48 ]. Nevertheless, cathepsin K is expressed in other oncocytic neoplasms, such as the recently described eosinophilic solid and cystic renal cell carcinoma [ 49 , 50 ]. These tumors may show overlapping morphological and immunohistochemical features with MiT family translocation renal cell carcinoma, especially with TFEB-rearranged renal cell carcinoma, both positive for cathepsin K and Melan-A.…”
Section: Discussionmentioning
confidence: 99%
“…Intestinal dysbiosis can enhance the release of LPS, which results in the production of cathepsin K (CTSK) in colorectal cancer (CRC) cells. Recent studies revealed a connection between the overexpression of CTSK and malignancies in colon cancer ( Li et al., 2019 ; Calio et al., 2021 ). Additionally, CTSK activates the mammalian target of rapamycin (mTOR) pathway by interacting with TLR4 on the macrophage, causing M2 polarization and the generation of cytokines including IL-4 and IL-10.…”
Section: The Gut Microbiota and The Host Immune Systemmentioning
confidence: 99%